Is there a correlation between benign paroxysmal positional vertigo and indirect sinus lifting - ATALI, ONUR; DERGİN, GÜHAN (My University, 2022)
Objective: The aim of this study is to inform surgeons regarding benign paroxysmal positional vertigo (BPPV) after indirect sinus lifting procedures and to assess its relationship with age, gender, residual alveolar bone height (RAB), and cortical thickness of the sinus floor. Methods: This study included 138 patients presenting for evaluation and management of BPPV after indirect sinus lifting. Patients with RAB lengths of 5–8 mm had been taken for indirect sinus lifting. Preoperative RAB length and cortical thickness of the sinus floor had been determined by cone beam computed tomography (CBCT) in each patient. The patients diagnosed with BPPV were promptly treated by an otolaryngologist. Data were assessed by descriptive statistical methods (mean ± standard deviation). Results were evaluated at the p<0.05 significance level, in 95% confidence interval (95% CI). Results: Totally 4 out of 138 of the patients showed BPPV. There was no statistically significant difference between the mean ages and gender ratio between the patients with BPPV [BPPV(+)] and without BPPV [BPPV(-)] groups. It was found that BPPV is 2.48 times more prevalent in patients with RAB criterion values <5.9 mm than in patients with criterion values >5.9 mm. BPPV is 4.54 times more prevalent in patients with a criterion cortical thickness value >0.8 mm than in patients with a criterion value <0.8 mm. Conclusion: Based on the results of this study, patients with cortical thickness values >0.8 mm should be informed before undergoing surgery, and patients exhibiting postoperative symptoms associated with vertigo should be treated promptly
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Reviews and References (medical); Research and Theory; Benign paroxysmal positional vertigo; maxillary sinus; osteotomy; Schneiderian membrane; FLOOR ELEVATION; MAXILLARY SINUS; OSTEOTOME; COMPLICATION; BONE; Benign paroxysmal positional vertigo; maxillary sinus; osteotomy; Schneiderian membrane